Financial globalisation uncertainty/instability is good for financial development - Simplice A. Asongu; Isaac Koomson; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2015)
Purpose - This study assesses the effect of time-dynamic financial globalisation uncertainty on financial development in 53 African countries for the period 2000-2011. Design/methodology/approach - Financial globalisation uncertainty is estimated as time-dynamic to capture business cycle disturbances while all dimensions identified by the Financial Development and Structure Database of the World Bank are employed, namely: financial depth (money supply and liquid liabilities), financial system efficiency (at banking and financial system levels), financial system activity (from banking system and financial system perspectives) and financial size. The empirical evidence is based on the Generalised Method of Moments with forward orthogonal deviations. Findings - The following findings are established. First, financial globalisation uncertainty does not significantly affect money supply, financial system deposits and financial size. Second, the uncertainty increases banking system efficiency, banking system activity and financial system activity. Moreover, the positive effects are consistently driven by above-median uncertainty levels. Practical implications- It follows that uncertainty in foreign capital flows may be a disguised advantage for domestic financial development, especially in dealing with the substantially documented issue of surplus liquidity in African financial institutions. Moreover, the sceptical view in the financial globalisation literature that 'allocation efficiency' is only plausible in the absence of uncertainty/instability is not substantiated by the findings. Justifications for the nexuses and other policy implications are discussed. Originality/value- To the best of our knowledge this is the first study to assess the effects of financial globalisation uncertainty on financial development in Africa using time-dynamic measurements of financial globalisation uncertainty and all dimensions identified by the Financial Development and Structure Database of the World Bank.
Keywords: F02; F21; F30; F40; O10; 330; Banking; Financial integration; Development